The Effect Of Ambience And Service Quality Of Coworking Space On Customer Satisfaction In Bandung City - Tjahjawati, Sri Surjani; Aliah, Santi; Sutisna, Ma’mun; Pramono, Tangguh Dwi; Leo, Gundur (Jurnal Ekonomi, 2024)
Coworking space is a shared workspace that is used as a place for startup workers, freelancers, and remote workers to support activities and increase work productivity. The high level of competition in the creative industry followed by a growing market share makes Coworking space in Bandung need to improve the atmosphere and quality of service to maintain its existence and grow. Coworking space users or consumers have increased from year to year causing entrepreneurs to compete for potential customers. This study aims to help coworking space entrepreneurs to find out the characteristics of coworking space users in the city of Bandung and the effect of atmosphere and service quality on customer satisfaction. The research method uses descriptive and analytical quantitative methods. Non probability sampling technique using purposive sampling with Lemeshow formula. The research data used primary data obtained through questionnaires from 141 respondents and secondary data obtained from literature studies. Data processing using IBM SPSS Statistics 23.0. The results of the analysis show that the atmosphere and quality of coworking space services have a positive and significant effect both simultaneously and partially on customer satisfaction in Bandung City. And obtained multiple regression equation Y = 5.084 + 0.151X1 + 0.347X2 where Y shows customer satisfaction, X1 shows the atmosphere, and X2  shows the quality of service.